Teknologi Otomasi dalam Industri Makanan-Studi Kasus: Optimalisasi Mesin Pencetak Bakso dengan Sistem Potong Berbentuk Sendok - Sindu Arifin, Kurniawan; Kristanto, Dedi; Prihartanto, Ari; Satria Praja, Alfreda (Program Studi Sistem Informasi Universitas Atma Jaya Yogyakarta, 2025)
The meatball industry in the Micro, Small, and Medium Enterprises (MSMEs) sector faces challenges in increasing production capacity and maintaining consistency in meatball size. This study aims to optimize a meatball forming machine with a spoon-shaped cutting system to improve production efficiency, size accuracy, and reduce reliance on manual labor. Testing was conducted by comparing manual and automatic meatball molding methods based on production speed, energy consumption, and mechanical durability. The results show that the machine can produce an average of 150 meatballs per minute, compared to the manual method, which only reaches 50-60 meatballs per minute. Furthermore, the machine's energy consumption of 500 watts per hour results in lower operational costs than the manual method, which requires additional labor. In terms of durability, the main components of the machine have a lifespan of more than 10 years with minimal maintenance. The study concludes that the implementation of an automatic meatball forming machine has a significant impact on MSMEs, improving productivity, reducing operational costs, and ensuring a more consistent product quality. Keywords: Meatball forming machine; production efficiency; spoon-shaped cutting system; MSMEs; automation